2023
DOI: 10.3389/fcvm.2022.1077279
|View full text |Cite
|
Sign up to set email alerts
|

Trend and early outcomes in isolated surgical aortic valve replacement in the United Kingdom

Abstract: ObjectiveSurgical aortic valve replacement (SAVR) is traditionally the gold-standard treatment in patients with aortic valve disease. The advancement of transcatheter aortic valve replacement (TAVR) provides an alternative treatment to patients with high surgical risks and those who had previous cardiac surgery. We aim to evaluate the trend, early clinical outcomes, and the choice of prosthesis use in isolated SAVR in the United Kingdom.MethodsAll patients (n = 79,173) who underwent elective or urgent isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
3
1
3
Order By: Relevance
“…Most importantly, we found that BPVs recently tended to be preferred over MPVs in patients between 50 and 60 years-old, a trend which is not observed to this extent in some other western countries ( 15 ). Added to patients aged from 60 to 65 years-old, they represent the so called middle-aged patients which represent a significant proportion (20%) of the overall population included in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Most importantly, we found that BPVs recently tended to be preferred over MPVs in patients between 50 and 60 years-old, a trend which is not observed to this extent in some other western countries ( 15 ). Added to patients aged from 60 to 65 years-old, they represent the so called middle-aged patients which represent a significant proportion (20%) of the overall population included in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…It would also be interesting to apply similar ensemble benchmarking approaches to identify the suitable models to use for combining variables and data from new cardiac interventions (e.g. TAVR 98 with that of historical interventions (SAVR) through clustering 99 and trajectory-based approaches. 100 102 …”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…Митрально-аортальная мембрана (7). Фиброзное кольцо митрального клапана (8). Передняя створка митрального клапана (9).…”
Section: потребность в задней аортопластике у взрослыхunclassified
“…Mitral-aortic membrane (7). Fibrous annulus of the mitral valve (8). Anterior leaflet of the mitral valve (9).…”
Section: потребность в задней аортопластике у взрослыхmentioning
confidence: 99%
See 1 more Smart Citation